Updating metacognitive control in response to expected retention intervals. - Fiechter, Joshua; Benjamin, Aaron (Memory & Cognition, 2017)
In five experiments, we investigated whether expected retention intervals affect subjects' encoding strategies. In the first four experiments, our subjects studied paired associates consisting of words from the Graduate Record Exam and a synonym. They were told to expect a test on a word pair after either a short or a longer interval. Subjects were tested on most pairs after the expected retention interval. For some pairs, however, subjects were tested after the other retention interval, allowing for a comparison of performance at a given retention interval conditional upon the expected retention interval. No effect of the expected retention interval was found for 1 min versus 4 min (Exp. 1), 30 s versus 3 min (Exp. 2), and 30 s versus 10 min (Exps. 3 and 4), even when subjects were given complete control over the pacing of study items (Exp. 4). However, when the difference between the expected retention intervals was increased massively (10 min vs. 24 h; Exp. 5), subjects remembered more items that they expected to be tested sooner, an effect consistent with the idea that they traded off efforts to remember items for the later test versus items that were about to be tested. Overall, this set of results accords with much of the test-expectancy literature, revealing that subjects are often reluctant to adjust encoding strategies on an item-by-item basis, and when they do, they usually make quantitative, rather than qualitative, adjustments.